Digital Media and Internet Safety Among Primary School Students During the Covid-19 Pandemic - Blažević, Ines; Klein, Nikolina (Revija za elementarno izobraževanje, 2022)
Digital media has become part of our everyday life in recent years, and this applies especially to school-age students. The COVID-19 pandemic and the transition to distance learning have raised the level of student exposure to the Internet, including its dangers. Aiming to examine the impact of preventive programs for safe Internet practices on the media literacy of children in primary school, we conducted an empirical study among 267 students. Media literacy was analysed in terms of the ways of using digital media as well as in terms of safe Internet practices, and comparisons were made by student gender and age.
Keywords: digital media, primary school students, COVID-19 pandemic, prevention programs, Internet safety